Influencing Pelvic Floor Changes on the Quality of Women’s Life During and Post Pregnancy - Liaqat Ali, Mahreen Iqbal, Muhammad Hanif, Faiza Hayat, Mujahid Khan, Muhammad Raheel (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Pelvic floor dysfunctions are widely acknowledged as one of the most serious public health issues, in terms of frequency, cost, and influence on quality of life of women. Over a third of females are believed to have pelvic floor diseases of varying severity at some point in their lives. Objective: To evaluate the influencing pelvic floor changes on the quality of women’s life during and post pregnancy. Methodology: This Multi-Centre cohort study was carried at the department of Urology & Transplantation, Institute of Kidney Diseases Peshawar, and Department of Gynaecology Jamrud Hospital Peshawar .The study duration was one year from June 2020 to June 2021 after approval of synopsis. A total of 45 women fulfilling the inclusion criteria were enrolled in our study. All the collection of data was carried out through predesigned questionnaire. Vaginal examination, translabial 2D/3D ultrasonography and a POP-Q test was done in the 3rd trimester of gestation and Three months after birth. The statistical analyses were performed using SAS software version 9.4. Results: In the current study, weakness of connective tissues was observed in 23 (51.1%) and Gestational diabetes was observed in 6 (13%). Amongst 45 women, vaginal deliveries were observed in 17 (37.78%), caesarean section in 17 (37.78%) while vacuum extraction deliveries were observed in 11 (24.44%) females. Two subjects were found to have LAM avulsion three months after their VE deliveries. Conclusion: Pelvic floor dysfunction is associated with connective tissue weakening and a larger fetus weight at delivery. To minimize future Pelvic floor problems, more women should seek postpartum care services.